Cemented versus uncemented hemiarthroplasty for displaced femoral neck fractures: A meta-analysis of randomized controlled trails. Issue 8 (February 2019) - Lin, Feng Fei; Chen, Yi Fang; Chen, Bin; Lin, Chao Hui; Zheng, Ke
Abstract: Background: The purpose of this meta-analysis was to compare the effectiveness and safety of cemented versus uncemented hemiarthroplasty for displaced femoral neck fractures. Methods: We searched PUBMED, EMBASE, Cochrane Library, and Google Scholar from their inception to February 2016. All RCTs comparing cemented with uncemented hemiarthroplasty for displaced femoral neck fractures were eligible. The participants who underwent primary hemiarthroplasty for unilateral femoral neck fracture were older than 55 and the mean age of more than 75 years old. For the trials before 2006 used old designed prostheses, so we excluded trails before 2006 which used old designed prostheses. Outcomes of interest include postoperative hip function, Harris hip score (HHS), mortality, reoperation rate, complications, operation time, intraoperative blood loss. Two reviewers independently evaluated the included studies and extracted data into RevMan. Quality Assessments were classified by agreement of 2 authors based on the Cochrane tool. Results: Seven trials were eligible. Postoperative hip function at 12 months cemented hemiarthroplasty was better than that in uncemented hemiarthroplasty (OR = 0.52, 95% CI, 0.31–0.88; P = .01). Postoperative fractures rates in cemented hemiarthroplasty were lower than that in uncemented hemiarthroplasty (OR = 0.09, 95% CI, 0.02–0.38; P = .001). Also, the interoperative fracture rates in cemented hemiarthroplasty were lower than that in uncemented hemiarthroplasty (OR = 0.29, 95% CI, 0.13–0.68; P = .004). Shorter operation time was achieved in uncemented hemiarthroplasty than that in cemented hemiarthroplasty (WMD = 8.22 min, 95% CI, 5.57–10.86 min; P <.00001). There was no significant difference between the 2 groups with HHS, mortality, wound infection, dislocation, general complications, reoperation rate, and intraoperative blood loss. Conclusion: The available evidence indicates that compared with uncemented hemiarthroplasty cemented hemiarthroplasty achieved better postoperative hip function, less postoperative, and interoperative fractures in displaced femoral neck fracture. Uncemented hemiarthroplasty achieved shorter operation time. There was no difference between the 2 groups with HHS at 1 year, mortality, and complications.